1996
DOI: 10.1177/0265407596131007
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Marital Satisfaction among Couples Coping with Chronic Constructive Airway Disease

Abstract: Couples in which one spouse has chronic obstructive airway disease (COAD) face great distress and change over the life course. Couples experience multiple losses and feelings of anxiety, depression and hopelessness, usually beginning in mid-life and continuing into older age. This study explored two sources of social support - family support and friend support - as resources for coping with illness. The relation of family and friend received and provided support with marital satisfaction and the effects of sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…A cohesive family may promote social support, preventing marital relationships from deteriorating because of stress‐related issues. The literature suggests that social support mitigates the harmful effects of life crises on marital satisfaction in Western (Unger, Jacobs, & Cannon, ) as well as Chinese societies (Chi et al, ). Therefore, family cohesion may serve as a critical buffer between midlife stress and marital satisfaction.…”
Section: Midlife Health Role Changes and Marital Satisfactionmentioning
confidence: 99%
“…A cohesive family may promote social support, preventing marital relationships from deteriorating because of stress‐related issues. The literature suggests that social support mitigates the harmful effects of life crises on marital satisfaction in Western (Unger, Jacobs, & Cannon, ) as well as Chinese societies (Chi et al, ). Therefore, family cohesion may serve as a critical buffer between midlife stress and marital satisfaction.…”
Section: Midlife Health Role Changes and Marital Satisfactionmentioning
confidence: 99%
“…Unger, Jacobs, and Cannon (1996) studied 100 couples with mixed respiratory diagnoses in which COPD predominated. Support from family was associated with better relationship satisfaction of the patients (of both genders) and also for female partners but not for male partners.…”
Section: Relationship Among the Variables Studied In Patients With CLmentioning
confidence: 99%
“…The results indicated that patient marital adjustment was associated with patient psychological well-being, and partner marital adjustment was associated with patient physical functioning. Unger, Jacobs, and Cannon (1996) studied 100 couples with mixed respiratory diagnoses in which COPD predominated. Support from family was associated with better relationship satisfaction of the patients (of both genders) and also for female partners but not for male partners.…”
Section: Relationship Among the Variables Studied In Patients With CLmentioning
confidence: 99%
“…However, many studies have demonstrated the weU-known stress-buffering effect of social support (for a review, see S. Cohen & Wills, 1985;LaRocco, House, & French, 1980). There is also some evidence for the stress-buffering hypothesis among patients with chronic disease (e.g., Koopman, Hernumson, Diamond, Angell, & Spiegel, 1998;Unger, Jacobs, & Cannon, 1996). Other researchers have investigated the possible moderating role of limitations in the daily functions of living with respect to the link between social support and patients' adjustment to chronic disease (Affleck, Pfeiffer, Tennen, & Fifield, 1988;Manne, Taylor, Dougherty, & Kemeny, 1997;Revenson, Wollman, & Felton, 1983).…”
mentioning
confidence: 99%